2010
DOI: 10.1021/ja104461p
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed EPR Determination of the Distance between Heme Iron and FMN Centers in a Human Inducible Nitric Oxide Synthase

Abstract: Mammalian NOS is a homodimeric flavo-hemoprotein that catalyzes the oxidation of L-arginine to NO. Regulation of NO biosynthesis by NOS is primarily through control of interdomain electron transfer (IET) processes in NOS catalysis. The IET from the FMN to heme domains is essential in the delivery of electrons required for O 2 activation in the heme domain and the subsequent NO synthesis by NOS. The NOS output state for NO production is an IET-competent complex of the FMN-binding domain and heme domain, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
142
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(161 citation statements)
references
References 76 publications
18
142
0
Order By: Relevance
“…This complex has been crystallized in four different conformations showing the flexible nature of the interdomain interactions. Edge to edge distances of 13 to 18 Å between the heme iron of one subunit and the FMN center of the other subunit of the iNOS dimer were recently determined using pulse EPR experiments [63]. These distances are in excellent agreement with IET kinetic studies [64,65], low temperature MCD data [66], and support the tethered shuttle model.…”
Section: Biophysical Studies To Characterize Cam Bound To the Nos Isosupporting
confidence: 59%
“…This complex has been crystallized in four different conformations showing the flexible nature of the interdomain interactions. Edge to edge distances of 13 to 18 Å between the heme iron of one subunit and the FMN center of the other subunit of the iNOS dimer were recently determined using pulse EPR experiments [63]. These distances are in excellent agreement with IET kinetic studies [64,65], low temperature MCD data [66], and support the tethered shuttle model.…”
Section: Biophysical Studies To Characterize Cam Bound To the Nos Isosupporting
confidence: 59%
“…Previous NOS computational modeling studies lacked the necessary experimental evidence to guide placement of calmodulin, and significant interaction between calmodulin and the heme domain had not been observed. Indeed, two studies omitted calmodulin entirely in their modeling (10,23). Whereas two other NOS modeling studies included calmodulin, neither reported direct interaction of calmodulin with the heme domain (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to define interactions between the heme and reductase domains using computational docking (9)(10)(11). However, selecting the catalytically relevant structure from many alternative models is difficult without direct experimental evidence delineating the protein-protein interfaces between the heme domain, FMN subdomain, and calmodulin.…”
mentioning
confidence: 99%
“…Structures of the nNOS reductase domain (8,16) and the iNOS FMN subdomain and CaM-binding helix bound to CaM (17) have also been reported. Previous computational docking studies (7,9,17,18) provide an emerging view of the output state in NOS holoenzymes, but these methods provide numerous models, and selecting the catalytically relevant structure or structures without direct experimental evidence is difficult. Our recent HDX-MS studies provided detailed models of the iNOS output state, but, because the FAD/NADPH subdomain was not included in the truncations used in this study, the relative positioning of the entire reductase and oxidase domains could not be determined (7).…”
Section: Significancementioning
confidence: 99%